Pengaruh Education Caregiver Terhadap Perilaku Pasien Asma - Sismulyanto; Dewi, Rini Puspita; Putra, Made Mahaguna (State Islamic University of Sunan Ampel, 2025)
Asthma is still a public health problem, asthma is considered a simple disease that is not dangerous and easy to treat. This study aims to determine the effect of caregiver education on the behavior of asthma patients in the Wongsorejo Health Center work area, Banyuwangi Regency. This research method uses a quasi-experimental design with a one-group retest-postest design approach. The sample of this study was part of the families of asthma patients at the Wongsorejo Health Center, Banyuwangi Regency, amounting to 56 respondents, the sample determination used the Random Sampling technique. The sample was divided into 28 treatment groups and 28 control groups. The independent variable is caregiver education, while the dependent variable is the behavior of the family of asthma patients. The results of the study with the Mann-Whitney U Test obtained p = 0.000 while the Wilcoxon Sign test obtained p = 0.005. It can be concluded that there are differences in the results in the two groups and the provision of caregiver education affects improving family behavior. Family involvement as a caregiver is the main factor that needs information, knowledge, and skills support while caring for asthma sufferers at home. So it is very important to improve family behavior in providing benefits in achieving relapse prevention behavior in family members who suffer from asthma.